1997
DOI: 10.1111/j.1399-0004.1997.tb02418.x
|View full text |Cite
|
Sign up to set email alerts
|

Two mosaic‐YY males carrying asymmetric Y chromosomes

Abstract: Two patients were referred because of oligospermia and azospermia, respectively. Karyotypic analysis revealed two mosaic‐YY males carrying asymmetric Y chromosomes. To our knowledge, no instance of double unequal Y chromosomes has been reported so far in human males. Results of fluorescent in situ hybridization (FISH) studies in spermatozoa from one of these patients revealed a significantly high number of hyperaploid spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is the first time that ultrastructural sperm analysis and FISH have been performed in a carrier of this type of mosaicism. Recently, a correlation between abnormal karyotypes and human male infertility has become more evident [6,7,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first time that ultrastructural sperm analysis and FISH have been performed in a carrier of this type of mosaicism. Recently, a correlation between abnormal karyotypes and human male infertility has become more evident [6,7,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…However, fluorescent in situ hybridization (FISH) studies in spermatozoa from carriers of sex chromosome mosaicism have revealed a significantly high number of hyperaploid spermatozoa [6,7] and these patients may risk producing offspring with an altered sex constitution.…”
Section: Introductionmentioning
confidence: 99%